Analysis of the application of the integral management in six commercial companies of family type in Florencia, Colombia - Hernández-Gil, Cristian; Vargas-Vargas, Beatriz Eugenia; Gutiérrez-Mora, Beatriz Eugenia; Figueroa-Ramírez, Edward Fabián; Correa-Corrales, Luis Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The integral management model has become one of the most complete organizational schemes that gather the strategic areas of an economic entity, based on three main components: quality, job security and environmental management. The purpose of this paper is to present the analysis of the application of the integral management in six commercial companies of family origin, in Florencia, Colombia. The problem lies in the lack of competitiveness and business development of the region which makes the non-existence of enough aspects to give credibility and value to its economy. A descriptive study based on a qualitative approach was carried out, where workers from three hierarchical levels ( strategical, tactical, and operational) of the six most recognized commercial companies of family origin in Florencia were interviewed. The results indicate that despite the absence of an explicit integral management model for these companies in the region, some progress in their construction is considered, oriented under the following elements: quality based on brand recognition, application of occupational health activities and basic recycling systems.